Imaging Findings of Solitary Plasmacytoma of the Cranium - Sukriti, Shrestha; Li, Zhu; Xinxiang, Zhao (Archives of Clinical and Medical Case Reports, 2018)
Solitary plasmacytoma of bone (SBP) are extremely rare and limited in the English literature. The most common locations in the skull are sphenoid bone, juxtasellar region, petrous apex and cerebral convexity or falx. SBP has higher risk of advancing to Multiple Myeloma within the duration of 2-4 years. Here we report two cases involving the cranium, both the cases initially mis-diagnosed as meningioma and after histopathology report confirmed as plasmacytoma. Further laboratory investigations were made to rule out multiple myeloma and its systemic involvement. We will also further discuss about the CT and MRI features and the most common differential diagnosis of SBP.